Penerapan Terapi Isometric Handgrip Exercise terhadap Penurunan Tekanan Darah pada Keluarga Hipertensi di Kecamatan Jebres Kota Surakarta - Rini Dwi Sukmawati; Tri Susilowati; Yohana Ika Prastiwi (Yayasan Literasi Sains Indonesia, 2026)
Background: Hypertension is a cardiovascular condition requiring long-term management. Non-pharmacological therapies, such as isometric handgrip exercises, offer a viable self-management option within the context of family care. Objective: To determine the outcomes of isometric handgrip exercise therapy in elderly individuals with hypertension. Methods: This study employed a pre-experimental design-specifically a one-group pre-test/post-test format-conducted as a case report involving two respondents (Mrs. W and Mr. M) in Guwosari Village, Jebres District, Surakarta. The intervention was administered over five consecutive days, once daily for 12 minutes (comprising four sets of 45-second isometric contractions with one-minute rest intervals between contractions). Data were analyzed using a descriptive quantitative approach, reporting mean values ​​and standard deviations (SD). Results: The baseline mean (pre-test) for Mrs. W was 148.0/85.0 mmHg (systolic SD 5.7; diastolic SD 4.9), which decreased to 136.2/81.8 mmHg post-intervention (systolic SD 8.0; diastolic SD 5.9). For Mr. M, the baseline mean (pre-test) was 146.6/88.4 mmHg (systolic SD 8.2; diastolic SD 7.1), which decreased to 137.4/82.2 mmHg post-intervention (systolic SD 6.1; diastolic SD 7.0). The average mean reduction in systolic blood pressure was 11.8 mmHg for Mrs. W and 9.2 mmHg for Mr. M. Conclusion: Isometric handgrip exercise is clinically beneficial for lowering and controlling blood pressure and is safe to use as an adjunct therapy that families can perform independently.